The Effect Of Service Quality And Price On Purchasing Decisions For Honda Genio Motorbikes At PT Nusantara Surya Sakti In Kubu Raya - Fikriansyah Fikriansyah; Sukardi Sukardi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine whether there is a relationship between quality and price on purchasing decisions. With a data collection strategy using a questionnaire and a sample size of 100 respondents, this study uses an associative methodology. Respondents are consumers who buy Honda Genio Motorbikes aged 17-50 years. The statistical methods used in the analysis include: multiple linear regression, correlation coefficient and determination, simultaneous test (F test), and partial test (t test). The data were linear, normally distributed, and showed no signs of multicollinearity; these findings were confirmed by the standard assumption tests. The variables have a strong relationship with each other, as indicated by the correlation value of 0.842. Based on the coefficient of determination (R2) value, the variables included in this study contributed 71.0% to the purchase decision, while the remaining 29% was influenced by other factors not included in this study. The study shows that service quality and price have a significant influence on purchasing decisions.